2018
DOI: 10.31878/ijcbr.2018.43.11
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effect of Diosgenin Against Carbon Tetrachloride and Cisplatin Induced Hepatotoxicity in Rats

Abstract: Background: Activation of hepatic stellate cells (HSC) plays central role in the development of liver fibrosis. In HSC activation, the transforming growth factor-β1 (TGF-β1) is considered to be the main stimuli factor. Diosgenin are the steroidal saponin and found in Trigonella foenum graecum Linn (Fenugreek) and some other species of Dioscorea. Diosgenin attenuates HSC activation by inhibiting transforming growth factor-β. Aim: In present study an attempt was made to explore the effect of diosgenin on liver f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…Damage to the hepatocytes promotes the release of enzymes into the bloodstream and ultimately causes an increase in the serum levels of AST and ALT [14]. The production of free radicals due to the hepatotoxic effects of CCL4 causes oxidative damage to the hepatocytes, thereby promoting the leakage of liver enzymes into the circulation [17]. Serum albumin level is an-other parameter determining liver function, which decreases in the end stage liver diseases.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Damage to the hepatocytes promotes the release of enzymes into the bloodstream and ultimately causes an increase in the serum levels of AST and ALT [14]. The production of free radicals due to the hepatotoxic effects of CCL4 causes oxidative damage to the hepatocytes, thereby promoting the leakage of liver enzymes into the circulation [17]. Serum albumin level is an-other parameter determining liver function, which decreases in the end stage liver diseases.…”
Section: Discussionmentioning
confidence: 99%
“…This steroidal sapogenin prevented liver fibrosis and ameliorated liver function. Diosgenin could decrease serum levels of liver enzymes, total bilirubin, and hydroxyproline [17]. Another study suggested that diosgenin is a potential agent to prevent the development of NAFLD and reduce serum ALT levels through the adenosine monophosphate-activated protein kinase (AMPK) and liver X receptor (LXR) signaling pathways [14].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Assessment of Biochemical paradigms such as AST, ALP, ALT, TB and HP was conducted as per the manufacturer's protocol and the literature avalable. 15…”
Section: Biochemical Parametersmentioning
confidence: 99%
“…Liver content of hydroxyproline and ECM deposition, prominent markers of liver fibrosis, were also reduced by diosgenin. Diosgenin, probably via inhibiting the activation of hepatic stellate cells (HSCs), prevented liver fibrosis development ( Nimbalkar et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%